Dual port temperature sensor tag for passive UHF RFID systems. Issue 2 (17th March 2014) - Virtanen, J.; Yang, F.; Ukkonen, L.; Elsherbeni, A.Z.; Babar, A.A.; Sydänheimo, L.
Abstract : Purpose: – The purpose of this paper is to develop a novel totally passive, wireless temperature sensor tag based on ultra high-frequency (UHF) radio frequency identification (RFID) technology. The temperature-sensing functionality is enabled by using distilled water embedded in the tag antenna substrate. The novel sensor tag is designed to provide wireless temperature readings comparable to a commercial thermocouple thermometer even in environments with high levels of interference, such as reflections. The structure of the novel sensor tag is aimed to increase its usability by minimizing user-created errors and to simplify the measurement procedure. Design/methodology/approach: – The sensor tag is based on a dual port sensing concept in which two ports are used to obtain sensor readings. By utilizing two ports instead of one, the effects of environmental interference, tag-reader antenna orientation and distance can be effectively minimized. Two alternative methods of acquiring the sensor reading from the operating characteristics of the two ports are presented and discussed. Findings: – Temperature measurements in practical scenarios show that by utilizing the dual port sensing concept, the developed tag produces temperature readings wirelessly which are comparable to readings from a commercial thermocouple thermometer. Research limitations/implications: – The concept of dual port sensing was shown and two alternative methods on extracting sensor readings from the differences in the port operating characteristics were introduced and discussed. In this paper, the dual port sensing concept is utilized in creating a temperature sensor tag; however, the same concept can be utilized in a variety of passive wireless sensors based on UHF RFID technology. This enables a new approach in designing accurate, easy to use and easily integrable passive sensors. The dual port sensing concept is in its early stages of development; its accuracy could be improved by developing more advanced data post-processing techniques. Practical implications: – The accuracy of a passive dual port UHF RFID-enabled temperature sensor tag is proven to be sufficient in many applications. This indicates that other sensor types utilizing the dual port sensing concept can reach high levels of accuracy as well. Furthermore, the passive RFID-enabled sensors based on the dual port sensing concept are superior in usability versus sensor tags equipped only with a single port. Therefore, dual port sensing concept in passive UHF RFID-enabled sensor tags could make such sensors more attractive commercially and lead to truly widespread ubiquitous sensing and computing. Originality/value: – This paper presents a novel passive, wireless temperature sensor tag for UHF RFID systems. The sensor tag utilizes a new structure which allows tight integration of two ports and two tag antennas. The accuracy of the developed tag is confirmed throughout measurements and it is found comparable to the accuracy of commercial thermometers in practical measurement scenarios. Moreover, the paper presents a dual port sensing concept and two readout methods based on the concept which are aimed to increase the accuracy and usability of all kinds of UHF RFID-enabled sensor tags.